MODE OF ACTION OF A POTENT SULPHYDRYL RADIOPROTECTOR MPG |N RADIOCALCIUM INDUCED DAMAGE IN SWISS ALBINO MICE - SHARMA, SUMAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Radiocalcium (Ca) being a radionuclide gets incorporated into the body and irradiate the tissues continuously. As it is in close contact with the tissues which it irradiate, minute quantities can produce serious effects. The histopathological/ biochemical changes produced by radiocalcium are modified to a considerable extent by Sulphydryll-MPG, a radioprotector.